MUTU PENGELOLAAN PROGRAM PENDIDIKAN PROFESI GURU (PPG) UNIVERSITAS PALANGKA RAYA - Abdul Rahman Azahari; Holten Sion; Wawan Kartiwa; Annur Qadariah (Program Studi Manajemen Pendidikan, FKIP Universitas Palangka Raya, 2022)
This study is a descriptive study that aims to describe the Quality of Management of the Teacher Professional Education (PPG) Program at the University of Palangka Raya in 2021. The population of this research are teachers, facilitators, and the PPG LMS Admins as many as 650 people. Considering the diverse population, both in type and quantity, the sampling and determination of samples is also carried out in various ways; so that the sample in this study consisted of 200 PPG participating teachers, 20 facilitators and 10 PPG LMS Admins. The technique used in collecting data in this research is by observing the results of the monitoring and evaluation of the learning implementation documents that have been carried out by PPG managers through the Quality Assurance Unit. The data analysis technique used is descriptive technique using non-parametric statistical techniques. The results showed that in general the quality of the management of the Teacher Professional Education Program (PPG) held at the University of Palangka Raya based on respondents' perceptions was in the